Peranan Sistem Keuangan Desa terhadap Kinerja Pemerintah Desa (Studi kasus di Desa Kapataran Kecamatan Lembean Timur Kabupaten Minahasa) - Watulingas, Patricia; Kalangi, Lintje; Suwetja, I Gede (Indonesia Accounting Journal, 2019)
The Village Financial System Application is a village financial management application system developed by the financial and development audit board or BPKP intended for village financial management. The purpose of this study is to determine the role of the Village Financial System or SISKEUDES on the performance of the village government in the village of Kapataran, the eastern Lembean district, Minahasa Regency. This research uses qualitative research. The data used are primary data in the form of interviews.The informants used were the village head and village secretary.The results showed that: (1) procedures for using SISKEUDES were carried out through 4 stages, namely planning, budgeting, administration, and bookkeeping; (2) ways to integrate low human resources (HR) through assistance and training; (3) the Village Financial System also has a purpose in assessing the performance of the village government. The SISKEUDES has important role to play in the village government which is felt directly by village officials. This is in accordance with the objectives of implementing the SISKEUDES, which is to assist work of village employees.